Can Providing Rubrics for Writing Tasks Improve Developing Writers' Calibration Accuracy?. Issue 4 (2nd October 2017) - Hawthorne, Katrice A.; Bol, Linda; Pribesh, Shana
ABSTRACT: Rubric-referenced calibration and the interaction between writing achievement and calibration, a measure of the relationship between one's performance and the accuracy of one's judgments, were investigated. Undergraduate students ( N = 596) were assigned to one of three calibration conditions: (a) global, (b) global and general criteria, or (c) global and detailed criteria. Students in all three conditions provided global predictions and postdictions of essay exam scores. Although calibration judgments by condition did not affect calibration accuracy overall, statistically significant main effects were found between calibration accuracy by criteria and prior achievement. High achievers made more-accurate predictions and postdictions by criteria than low achievers. Regardless of achievement level, those students in the detailed rubric condition had higher postdictive accuracy for the organization criteria than did students in the general rubric condition.